Incentive Compatibility in Bargaining Under Uncertainty - Chatterjee, Kalyan (Quarterly Journal of Economics, 1982)
Journal Article Incentive Compatibility in Bargaining Under Uncertainty Get access Kalyan Chatterjee Kalyan Chatterjee Pennsylvania State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 97, Issue 4, November 1982, Pages 717–726, https://doi.org/10.2307/1885109 Published: 01 November 1982